Competition and collusion among criminal justice and non-state actors in Brazil’s prison system - Macaulay, Fiona (Carceral communities in Latin America, 2021)
This chapter examines competition and collusion among criminal justice institutions and non-state actors in imprisonment in prisons in Brazil to analyse how both formal and informal dispositions and practices have created and sustain the mass incarceration that is a pre-condition for extensive prisoner self-governance. The chapter thus looks from the outside-in, examining how relationships between extra-mural institutions have created and sustained such an enormous prison population in Brazil. It also analyses these institutions and organisations as intra-mural actors that, through their action or inaction, exercise a key role in shaping the carceral experience for inmates. It highlights the competition between the different actors involved in the penal arena for control of the carceral space and of prisoners, driven by a variety of motives—rent-seeking, moral/philosophical, and territorial.